2022
DOI: 10.1073/pnas.2202803119
|View full text |Cite
|
Sign up to set email alerts
|

Septins mediate a microtubule–actin crosstalk that enables actin growth on microtubules

Abstract: Cellular morphogenesis and processes such as cell division and migration require the coordination of the microtubule and actin cytoskeletons. Microtubule–actin crosstalk is poorly understood and largely regarded as the capture and regulation of microtubules by actin. Septins are filamentous guanosine-5'-triphosphate (GTP) binding proteins, which comprise the fourth component of the cytoskeleton along microtubules, actin, and intermediate filaments. Here, we report that septins mediate microtubule–actin crossta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…7 ). Our data provide a starting point to expand further investigations with a particular focus on actin–microtubule intersections ( Nakos et al, 2022 ).…”
Section: Discussionmentioning
confidence: 79%
“…7 ). Our data provide a starting point to expand further investigations with a particular focus on actin–microtubule intersections ( Nakos et al, 2022 ).…”
Section: Discussionmentioning
confidence: 79%
“…Septins are well-equipped to mediate cytoskeletal crosstalk since they can bind to the cell membrane, actin and microtubules. 262 Recent research demonstrated roles of septins in mesenchymal and amoeboid single-cell migration 263,264 and in the regulation of endothelial and epithelial cell–cell adhesion. 265,266 Elucidating the biophysical mechanisms by which cytoskeletal crosstalk regulates cell migration is challenging due to the enormous molecular complexity of the cell and feedback between mechanical forces and biochemical signaling.…”
Section: The Road Aheadmentioning
confidence: 99%
“…Septins are GTP-binding proteins which form hetero-hexa- or hetero-octamers that can assemble into filaments; they have diverse functions including membrane curvature sensing, or the regulation of actin and MT dynamics; in axons, they were demonstrated to regulate cargo transport, growth, branching and calcium homeostasis ( Hu et al, 2012 ; Ageta-Ishihara et al, 2013 ; Spiliotis, 2018 ; Katz et al, 2019 ; Deb et al, 2020 ; Woods and Gladfelter, 2021 ; Nakos et al, 2022 ).…”
Section: Roles and Regulations Of The Cytoskeleton In Axonsmentioning
confidence: 99%